Effect of Spheroid Anneal 810oC and Double Annealing at 400oC to The Mechanical Properties and Microstructure of SUS 304 Thin Metal Foils for Sensor and Electronic Application - Aziz, Abdul; Suryanaa, Suryanaa; Pramono, Agus; Partuti, Tri; Hasanah, Indah Uswatun; Alhamidi, Ahmad Ali (Trends in Mechanical Engineering Research, 2024)
The stainless steel thin metal foils have wide application, especially for electronic industries. The problem hindered are high cost for mass production, the effect of phase transformation to the mechanical properties still not clear. The change of microstructure in austenitic stainless steel (ASS) after double annealing at 400oC and spheroid anneal treatment at 810oC in thin metal foils (TMF) of SUS 304 were studied experimentally, including Scanning Electron Microscope – Electron Back scaterred Difraction (SEM – EBSD) and five stages of the uniaxial tensile stress state. The martensitic phase transformation (MPT) and grain misorientation (GMO) compared each other both in fine grains and coarse grains. The MPT occur in ASS SUS 304 TMF. The GMO occur in SUS 304 Thin Metal Foils. The GMO spread homogeneous in fine grains and spread inhomogeneous in coarse grain. The GMO volume fractions in fine grains spread homogeneously. The GMO volume fractions in coarse grain spread inhomogeneously.